(untitled) (Boletin Médico de Postgrado, 2017)
Dengue fever is a viral disease that causes a considerable degree of morbidity and mortality, so it is important to know the risk factors. For this reason, a descriptive cross-sectional study was conducted in order to characterize the risk factors for severe dengue patients admitted to the Pediatric Intensive Care Unit of the Decentralized Service Pediatric Hospital Dr. Agustín Zubillaga. To this end, a series of 26 cases of severe dengue was selected, which were characterized by an average age of 5.11 ± 2.70 years, with a predominance of students (38.46%) and young infants (30,77%); and female (53.85%). In addition, 50% reported comorbidities (asthma and allergic rhinitis); however, 15.38% reported dengue without warning signs by reference. Furthermore, physical environmental factors were 96.15% had water storage, 73.08% presence of rain in recent days and 57.69% live in urban areas; biological factors such as the presence of vector 93.31% and 69.23% breeding sites found. Also, 93.31% have potable water, sewage disposal 73.08%, 65.38% toilet service, 100% 43.31% electricity and telephone. Among the highlights socioeconomic characteristics were 46.15% and 43.31% skilled worker unskilled, the educational level of the mother was a high school (50%) and 80.77% had weekly wage. The housing conditions were wall block (88.46%), zinc roof (43.31%) and cement floor (76.92%), with less than three rooms (76.92%) and less than 5 persons per household (65.38%), with an average residence time of 3.87 ± 2.73 years. 46.15% resulting meet some spacious optimal sanitary conditions and socioeconomic status was working class (46.15%) and low (43.31%) middle class. We conclude that this health problem is related to the residential environment and the existence of vector breeding sites. KEY WORDS: Severe dengue; risk factors, social-economic conditions.